2013
DOI: 10.1248/bpb.b12-00850
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein 6-<i>O</i>-β-d-Glucopyranuronoside Is a Main Metabolite in the Plasma after Oral Administration of Baicalin, a Flavone Glucuronide of Scutellariae Radix, to Rats

Abstract: Baicalin (BG) and its aglycone, baicalein (B) are strong antioxidants that exert various pharmacological actions and show unique metabolic fates in the rat. The aim of the present study was to identify major metabolite(s) besides BG in rat plasma after oral administration of BG or B. The main metabolite was detected by HPLC equipped with an electrochemical detector at a potential of +500 mV and identified as baicalein 6-O-β-d-glucopyranuronoside (B6G) by HPLC/MS/MS. When BG at a dose of 20 mg/kg was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…After oral administration of SR for 5 days in rat model, the level of PGE2 in LPS-stimulated macrophages was reduced robustly, and the pharmacodynamic interaction was proposed to be via the Cox–2 pathway 40 . The major metabolites were reported to be baicalin and baicalein by utilizing HPLC coupled with electrochemical detector 41 . From the results, AUC 0–24 hour values were 1.66 ± 0.34 µM and 19.8 ± 3.9 µM for baicalin, and 0.853 ± 0.065 µM and 10.0 ± 3.1 µM for baicalein, respectively 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral administration of SR for 5 days in rat model, the level of PGE2 in LPS-stimulated macrophages was reduced robustly, and the pharmacodynamic interaction was proposed to be via the Cox–2 pathway 40 . The major metabolites were reported to be baicalin and baicalein by utilizing HPLC coupled with electrochemical detector 41 . From the results, AUC 0–24 hour values were 1.66 ± 0.34 µM and 19.8 ± 3.9 µM for baicalin, and 0.853 ± 0.065 µM and 10.0 ± 3.1 µM for baicalein, respectively 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The major metabolites were reported to be baicalin and baicalein by utilizing HPLC coupled with electrochemical detector 41 . From the results, AUC 0–24 hour values were 1.66 ± 0.34 µM and 19.8 ± 3.9 µM for baicalin, and 0.853 ± 0.065 µM and 10.0 ± 3.1 µM for baicalein, respectively 41 . Furthermore, the pharmacokinetic parameters of baicalin and baicalein, after oral administration of SR, were calculated and analyzed by the pharmacokinetic program 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of nuclear localization of NRF2 in oxidative injury by administration of baicalin analog baicalein has been reported earlier in HepG2 cells and cisplatin nephrotoxicity [ 42 , 43 ]. After administration of baicalein, it modified mainly to its glucuronide analog baicalin in the blood stream with significantly stability (half-life of 11.8 hours) [ 44 , 45 ]. One of the important findings is that the absence of NRF2 can exacerbate NF- κ B activity leading to increased cytokine production, whereas NF- κ B can modulate NRF2 transcription and activity.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that when given by oral administration, glucuronidation of absorbed baicalein in liver could form large amount of baicalin (Akao et al, 2000(Akao et al, , 2013, which is also a strong antioxidant that exerts various pharmacological actions in rats. Furthermore, it was reported that oral administration of baicalein has hapatoprotective effects against CCl 4 -induced liver injury in mice and rats (Huang et al, 2012;Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%